Engineering the Surface and Mechanical Properties of Water Desalination Membranes Using Ultralong Carbon Nanotubes - Yehia M. Manawi; Kui Wang; Viktor Kochkodan; Daniel J. Johnson; Muataz A. Atieh; Marwan K. Khraisheh (Membranes, 2018)
In this work, novel polysulphone (PS) porous membranes for water desalination, incorporated with commercial and produced carbon nanotubes (CNT), were fabricated and analyzed. It was demonstrated that changing the main characteristics of CNT (e.g., loading in the dope solutions, aspect ratio, and functionality) significantly affected the membrane properties and performance including porosity, water flux, and mechanical and surface properties. The water flux of the fabricated membranes increased considerably (up to 20 times) along with the increase in CNT loading. Conversely, yield stress and Young’s modulus of the membranes dropped with the increase in the CNT loading mainly due to porosity increase. It was shown that the elongation at fracture for PS/0.25 wt. % CNT membrane was much higher than for pristine PS membrane due to enhanced compatibility of commercial CNTs with PS matrix. More pronounced effect on membrane’s mechanical properties was observed due to compatibility of CNTs with PS matrix when compared to other factors (i.e., changes in the CNT aspect ratio). The water contact angle for PS membranes incorporated with commercial CNT sharply decreased from 73° to 53° (membrane hydrophilization) for membranes with 0.1 and 1.0 wt. % of CNTs, while for the same loading of produced CNTs the water contact angles for the membrane samples increased from 66° to 72°. The obtained results show that complex interplay of various factors such as: loading of CNT in the dope solutions, aspect ratio, and functionality of CNT. These features can be used to engineer membranes with desired properties and performance.